2007
DOI: 10.1128/jvi.01606-06
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Mutant with Decreased Sensitivity to Ribavirin: Implications for Error Catastrophe

Abstract: The nucleoside analogue ribavirin (R) is mutagenic for foot-and-mouth disease virus (FMDV). Passage of FMDV in the presence of increasing concentrations of R resulted in the selection of FMDV with the amino acid substitution M296I in the viral polymerase (3D). Measurements of progeny production and viral fitness with chimeric viruses in the presence and absence of R documented that the 3D substitution M296I conferred on FMDV a selective replicative advantage in the presence of R but not in the absence of R. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
226
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(235 citation statements)
references
References 80 publications
9
226
0
Order By: Relevance
“…3). Interestingly, loop ␤9-␣11 contains the site of a mutation (M296I) found in ribavirin-resistant FMDV (27). The structural comparisons of the four FMDV 3D elongation complexes determined in this work as well as the comparisons with the FMDV polymerase structures determined previously (12) revealed that loop ␤9-␣11 is flexible, and its flexibility seems to be required to adapt its conformation and interactions to the size and shape of the different template bases and incoming nucleotides during the RNA elongation process ( Fig.…”
Section: Incorporation Of Mutagenic Nucleotide Analogs By Fmdv 3d: Immentioning
confidence: 99%
“…3). Interestingly, loop ␤9-␣11 contains the site of a mutation (M296I) found in ribavirin-resistant FMDV (27). The structural comparisons of the four FMDV 3D elongation complexes determined in this work as well as the comparisons with the FMDV polymerase structures determined previously (12) revealed that loop ␤9-␣11 is flexible, and its flexibility seems to be required to adapt its conformation and interactions to the size and shape of the different template bases and incoming nucleotides during the RNA elongation process ( Fig.…”
Section: Incorporation Of Mutagenic Nucleotide Analogs By Fmdv 3d: Immentioning
confidence: 99%
“…The results indicated that PRRSV is highly sensitive to ribavirin, since it accumulates more lethal mutations by mistakenly incorporating ribavirin. For other RNA viruses, it has been reported that poliovirus can tolerate consecutive in vitro passages at 600 mM ribavirin, foot-mouth disease virus (FMDV) at 800 mM, and human enterovirus 71 at 1600 mM (Sadeghipour et al, 2013;Sierra et al, 2007;Vignuzzi et al, 2006). The high sensitivity of PRRSV to ribavirin suggested a potential usage as an antiviral to inhibit PRRSV infection (Kim & Lee, 2013).…”
mentioning
confidence: 99%
“…In this study, two different amino acid substitutions were identified, each from a different PRRSV strain, which also occurred in some other RNA viruses. For example, by using different strains of FMDV, one study identified one substitution (M296I) while other independent studies identified three (P44S, P169S and M296I) or four (D5N, A38V, M194I and M296V) different substitutions that confer resistance to ribavirin and increased fidelity (Agudo et al, 2010;Sierra et al, 2007;Zeng et al, 2014). A couple of amino acid mutations were also identified in coxsackievirus B3 virus, human enterovirus 71 virus and bovine viral diarrhea virus (Curti & Jaeger, 2013;Gnädig et al, 2012;Sadeghipour et al, 2013).…”
mentioning
confidence: 99%
“…Despite the high error rates of RNA viruses, there are also some examples of the selection of strains with increased mutation rates when the environmental conditions vary drastically, as happens with changes in the host where the virus replicates (Schultz et al 1991;Suárez et al 1992), or during treatment with antiviral agents (Mansky & Bernard 2000). In this sense, a striking example is the selection of a mutant of foot-and-mouth disease virus (FMDV), which has a modestly lower fidelity polymerase that provides increased resistance to treatment with ribavirin (Sierra et al 2007;Arias et al 2008). These findings raise the question of whether there could be situations where an increase in the error rate by artificial means could have adaptive benefits for RNA viruses.…”
Section: Benefits Of Increased Mutagenesismentioning
confidence: 99%
“…The symbols represent the titres of the lytic plaques isolated from the supernatants obtained for each AZC concentration. (Wainberg et al 1996;Pfeiffer & Kirkegaard 2003;Vignuzzi et al 2006) or an enhanced ability to discriminate between the correct nucleotide and the mutagenic analogue (Sierra et al 2007). The evolution of mutational robustness by the selection of genotypes in which mutations have less negative impact is another possibility that must be taken into consideration , although the selection of this strategy possibly involves much longer times than those taking place during mutagen exposure (Martín et al 2008).…”
Section: Selection Of Resistance Mechanisms To Mutagenic Agentsmentioning
confidence: 99%